Role of Santri Middle Class in Democratization Process in Indonesia - Agus Darmaji (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2019)
Research on the Roleof Santri Middle Class in Democratization Process in Indonesia was conducted in three cities in Java, i.e. the Cities of East Jakarta, Yogyakarta, and Surabaya. The research was conducted by using quantitative approach and survey method. The data collection method used in this research is direct interview technique, by using questionnaire instrument that was asked to the respondents directly through face to face.There are two types of hypotheses to be proved through this survey research, they are associative and comparativehypotheses.The associative hypothesis verification aims to prove whether there is significant relationship between dependent variable (Y) and independent variable (X) as predictor or not. Inthis research context, the relationship between role in the democratization process as the dependent variable (Y) with predictor independent variables(X) will be tested, which are the literacy of political and economic information(X1), satisfaction to public services (X2), trust in democratic institutions (X3), access to political resources (X4), ideology (X5), and relative deprivation (X6).The comparative hypothesisverificationaims to prove whether there is significant difference between two or more different respondent groups or not. Based on this research purpose, the differences of two respondent groups will be proved comparatively related to their role in the democratization process; they are (1) santrimiddle-class group and (2) groups of santrinon-middle class.There are two types of hypotheses to be proved through this survey research, they are associative and comparative hypotheses. The associative hypothesis verification aims to prove whether there is significant relationship between dependent variable (Y) and independent variable (X) as predictor or not. In this research context, the relationship between role in the democratization process as the dependent variable (Y) with predictor independent variables (X) will be tested, which are the literacy of political and economic information (X1), satisfaction to public services (X2), trust in democratic institutions (X3), access to political resources (X4), ideology (X5), and relative deprivation (X6). The comparative hypothesis verification aims to prove whether there is significant difference between two or more different respondent groups or not. Based on this research purpose, the differences of two respondent groups will be proved comparatively related to their role in the democratization process; they are (1) santri middle-class group and (2) groups of santri non-middle class.From the result of hypothesis associative verification, it is proved that all variables X correlated positively and significantly to variable Y. With this result, then the literacy of political and economic information (X1), satisfaction to public services (X2), trust in democratic institutions (X3), access to political resources (X4), ideology (X5), and relative deprivation (X6) are proved to correlate positively and significantly to the role in democratization (Y).From the result of comparative hypothesis verification, the X2 value of 1363.44 is obtained. This value is greater than the X2 value of table at 88 degrees of freedom and significance level of 0.5. With this result, then the null hypothesis which stated that there is no significant difference between santri middle class and other class groups is rejected. This means the alternative hypothesis that stated otherwise is received. Conclusion based on this examination result is that there are significant differences between the role of santri middle class and other group samples in the democratization process.